Agropolitan Area Development Strategy Based on Corn Commodities in Malaka District East Nusa Tenggara Province - Klau, Anggelina Delviana; Rustiadi, Ernan; Siregar, Hermanto (International Journal of Scientific Research in Civil Engineering, 2019)
Agropolitan area planning is one of the efforts to accelerate rural and agricultural development, where cities are the center of the region with the availability of resources, growing and developing accessing, serving, encouraging and encouraging agribusiness ventures in regional villages and surrounding villages (hinterland). . The data used in this study are primary data. Primary data were obtained and collected from surveys and interviews with 6 expert respondents. Selection of expert respondents. The analysis technique used is the SWOT analysis (strengths, weaknesses, opportunities, and threats) to identify the agropolitan area development strategy and AHP (Analytical Hierarchy Process) for determining the priority of agropolitan area development strategies. The results of the analysis show that the development strategies sorted by priority are (1) Development and improvement of facilities and infrastructure for improving agriculture (STA, farm roads, irrigation, public facilities improvement), providing training for agribusiness development and strengthening institutional capital, (2) Utilize and maximize the potential advantages of existing natural resources and human resources so as to increase production to fill domestic and international markets and optimize government authority in empowering resources and partnership potential (3) Enhancing the role of government in protecting agricultural land, empowering farmer groups related to cultivation / farming and marketing that is able to increase the competitiveness of the agricultural products (4) Procurement of training for farmers related to the use of appropriate technology.